Influence of Dispersion Interactions on the Thermal Desorption of Nonplanar Polycyclic Aromatic Hydrocarbons on HOPG - Weippert, Jürgen; Huber, Philipp; Schulz, Ayla; Amsharov, Konstantin; Böttcher, Artur; Kappes, Manfred M. (Physica Status Solidi-Rapid Research Letters, 2019)
A combination of low energy ion beam deposition and mass resolved thermal desorption spectroscopy is applied to analyze the binding behavior of two nonplanar polycyclic aromatic hydrocarbons (PAHs) to highly oriented pyrolytic graphite (HOPG) surfaces—also concerning their lateral dispersion interactions. In particular, the fullerene precursor C60H30 (FPC) and rubrene C42H28 are studied. Due to their smaller contact areas, both molecules exhibit significantly weaker binding energies to the HOPG surface compared to planar PAHs of similar size: C60H30 is bound to the surface by 3.04 eV, which is 0.6 eV lower than for a fully planar homologue. For rubrene, an isolated molecule–substrate binding energy of 1.59 eV is found, which is about 1 eV less than that of the corresponding planar homologue hexabenzocoronene C42H18. In contrast to FPC, rubrene shows a significant (intermolecular) lateral dispersion contribution to the binding energy as the submonolayer coverage increases.
CRIS-Team Scopus Importer:2019-09-03
Keywords: atomic force microscopy; desorption; dispersion; polycyclic aromatic hydrocarbons; Runge–Kutta integration; temperature-programmed desorption